Initial agglomeration of non-wetted solid particles in high temperature melt. (16th March 2019) - Duan, Haojian; Ren, Ying; Zhang, Lifeng
Graphical abstract: Highlights: Activation energy and stable energy increase with the separation distance between particles. Activation separation distance and critical separation distance are directly proportional to particle radius. Equilibrium energy is a quadratic function of particle radius. Agglomeration of non-wetted solid particles in the high temperature melt is derived from the cavitation between particles. Abstract: Based on the bridge cavitation theory, the free energy variation during the cavitation between two non-wetted solid particles in a high temperature melt was investigated. The activation state and the stable state were achieved at the maximum and the minimum of the free energy curve varying with the neck radius, respectively. Increasing the separation distance between particles, both the activation energy and the stable energy increased. The activation separation distance was defined as the separation distance at which the extremum of the total free energy with respect to the neck radius had disappeared and the critical separation distance was derived by equaling the free energy before and after the cavitation. When particles were contacting, an equilibrium state was obtained as the system energy reached its minimum value. The equilibrium energy was the energy when the energy drop for the cavitation reached its maximum value. It is novel for the present study to find that both the activation separation distance and the critical separation distance were directly proportional to the radius of particles. Meanwhile, the equilibrium energy was a quadratic function of the particle radius. In the case of the cavitation between two 5.0 μm alumina particles in the molten steel, the activation separation distance, the critical separation distance and the equilibrium energy were 0.96 μm, 0.73 μm and 17.75 × 10 −12  J, respectively. Furthermore, a comparison between the calculation and experimental results showed a good agreement.